Factors influencing the social participation ability of rural older adults in China: A cross-sectional study - Cheng, Minghui; Su, Wenli; Li, Huiju; Li, Linjie; Xu, Minghui; Zhao, Xue; Han, Mengdie; Yang, Li (Frontiers in Public Health, 2023)
Objective To investigate the epidemiology and influencing factors of social participation ability of rural older adults in China. Methods From March to April 2021, 3450 older adults in poverty aged 60 and above registered in Jishishan County (J County) were selected by cluster sampling for a cross-sectional questionnaire survey and their social participation ability was assessed using the Ability Assessment of older adults (MZ/T039-2013). The results were statistically analyzed and an ordered multi-category logistic regression analysis was used to analyze the effect of influencing factors on the social participation ability of rural older adults. Results 3,346 questionnaires were collected, with an effective recovery rate of 96.99%. Out of all the participants, 1,355 (40.5%) of the 3,346 cases had intact social participation ability, while 1,991 (59.5%) had different degrees of loss of social participation ability, of which 1,393 (41.14%) were mildly impaired, 419 (12.5%) were moderately impaired and 179 (5.3%) were severely impaired. Age, educational level, religious belief, living status, whether suffering from dementia and the occurrence of accidents in recent 30 days were influencing factors on the social participation ability (p < 0.05). Conclusion The rate of impaired social participation ability among older adults was >50% and age, educational level, religious beliefs, living status, whether suffering from dementia, and the occurrence of accidents in recent 30 days (such as falls, choking, loss) were significant factors influencing the ability of social participation of rural older adults.